Human peptide α‐defensin‐1 interferes with Clostridioides difficile toxins TcdA, TcdB, and CDT. Issue 5 (19th March 2020) - Fischer, Stephan; Ückert, Anna‐Katharina; Landenberger, Marc; Papatheodorou, Panagiotis; Hoffmann‐Richter, Carola; Mittler, Ann‐Katrin; Ziener, Ulrich; Hägele, Marlen; Schwan, Carsten; Müller, Martin; Kleger, Alexander; Benz, Roland; et al.
Abstract: The human pathogenic bacterium Clostridioides difficile produces two exotoxins TcdA and TcdB, which inactivate Rho GTPases thereby causing C. difficile ‐associated diseases (CDAD) including life‐threatening pseudomembranous colitis. Hypervirulent strains produce additionally the binary actin ADP‐ribosylating toxin CDT. These strains are hallmarked by more severe forms of CDAD and increased frequency and severity. Once in the cytosol, the toxins act as enzymes resulting in the typical clinical symptoms. Therefore, targeting and inactivation of the released toxins are of peculiar interest. Prompted by earlier findings that human α‐defensin‐1 neutralizes TcdB, we investigated the effects of the defensin on all three C. difficile toxins. Inhibition of TcdA, TcdB, and CDT was demonstrated by analyzing toxin‐induced changes in cell morphology, substrate modification, and decrease in transepithelial electrical resistance. Application of α‐defensin‐1 protected cells and human intestinal organoids from the cytotoxic effects of TcdA, TcdB, CDT, and their combination which is attributed to a direct interaction between the toxins and α‐defensin‐1. In mice, the application of α‐defensin‐1 reduced the TcdA‐induced damage of intestinal loops in vivo. In conclusion, human α‐defensin‐1 is a specific and potent inhibitor of the C. difficile toxins and a promising agent to develop novel therapeutic options against C. difficile infections.